2016
DOI: 10.1177/1468794116630040
|View full text |Cite
|
Sign up to set email alerts
|

Arts-based health research and academic legitimacy: transcending hegemonic conventions

Abstract: Using the Canadian context as a case study, the research reported here focuses on in-depth qualitative interviews with 36 researchers, artists and trainees engaged in 'doing' arts-based health research (ABHR). We begin to address the gap in ABHR knowledge by engaging in a critical inquiry regarding the issues, challenges and benefits of ABHR methodologies. Specifically, this paper focuses on the tensions experienced regarding academic legitimacy and the use of the arts in producing and disseminating research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 47 publications
1
88
0
1
Order By: Relevance
“…Our observations are consistent with a fundamental tension between the demands of research and the capacity of the community, similar to the tensions described by Boydell et al (2016) in the context of arts-based health research (i.e., balancing structure vs. openness and flexibility; fulfilling academic obligations of truth and accuracy; resisting typical notions of what counts in academia; and managing expectations vis-à-vis measuring the impact). Tensions have been resolved through strong and respectful collaboration between community and academy.…”
Section: Discussionsupporting
confidence: 88%
“…Our observations are consistent with a fundamental tension between the demands of research and the capacity of the community, similar to the tensions described by Boydell et al (2016) in the context of arts-based health research (i.e., balancing structure vs. openness and flexibility; fulfilling academic obligations of truth and accuracy; resisting typical notions of what counts in academia; and managing expectations vis-à-vis measuring the impact). Tensions have been resolved through strong and respectful collaboration between community and academy.…”
Section: Discussionsupporting
confidence: 88%
“…Sinner et al (2006) noted how the validity of arts-based research approaches may still be questioned in some circles, Atkins (2013) revealed how she and her graduate students had to explain and justify their use of arts-based research to suspicious colleagues, and Moon (2013) described his experience of artistic modes of inquiry being dismissed by art therapy educators and researchers. In advocating for arts-based health research as a scholarly activity worthy of recognition, Boydell et al (2016) explored aspects of academic legitimacy that debated structure versus flexibility in the research process, truth and accuracy in the representations of research in art, and traditional versus innovative academic contributions and impacts. They commented that in health research the biomedical model and traditional positivist empiricism make it difficult to receive recognition for arts-based research, which draws upon a constructivist philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…We planned to use tried and tested methods for collecting and analysing data, such as scaled attitude measures with open questions for the survey of societal attitudes, and individual narrative interviews with participants using photovoice. One of the struggles and tensions in participatory action research is balancing the needs and requirements of funding bodies and the research institutions, with the goal of social transformation and active participation (Boydell et al, 2016). We planned to report results for a non-academic audience, making findings accessible so as to raise public awareness of issues of disability and sexuality.…”
Section: Participatory Researchmentioning
confidence: 99%
“…We planned to report results for a non-academic audience, making findings accessible so as to raise public awareness of issues of disability and sexuality. But we also planned to publish papers in academic journals, so that this affords the project "academic legitimacy" (Boydell et al, 2016). However, we also considered this as a form of action for change, in that publishing on matters related to disability and sexuality in academic journals, brings attention to the limited publications in sexuality research (Rohleder & Swartz, 2012).…”
Section: Participatory Researchmentioning
confidence: 99%